Aspek Pengembangan Peserta Didik: Kognitif, Afektif, Psikomotorik - Hamzah, Syeh Hawib (Fakultas Tarbiyah dan Ilmu Keguruan, Universitas Islam Negeri Sultan Aji Muhammad Idris Samarinda, 2012)
Education is the most important thing to students as guidance to go through the life. In this case, education process has to be designed specifically in terms of students’ development of cognitive, affective, and psychomotor competence. These three aspects need to be developed comprehensively so that academic, social, and creative competence of students can be maximally actualized.